2011
DOI: 10.1534/genetics.110.123117
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Regulation of CenH3 Localization and Histone H3 Turnover by CAF-1 and HIR Proteins in Saccharomyces cerevisiae

Abstract: Accurate chromosome segregation is dependent on the centromere-specific histone H3 isoform known generally as CenH3, or as Cse4 in budding yeast. Cytological experiments have shown that Cse4 appears at extracentromeric loci in yeast cells deficient for both the CAF-1 and HIR histone H3/H4 deposition complexes, consistent with increased nondisjunction in these double mutant cells. Here, we examined molecular aspects of this Cse4 mislocalization. Genome-scale chromatin immunoprecipitation analyses demonstrated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 70 publications
(110 reference statements)
0
38
1
Order By: Relevance
“…In multiple studies, yeast lacking various histone chaperones exhibit slowed H3/H4 turnover dynamics. This has been observed globally for Asf1 Kaplan et al 2008), Rtt106 (Imbeault et al 2008), and the CAF-1 and Hir complexes (Rosa et al 2010), although spt16 mutants, as cited above, do show increased turnover (Jamai et al 2009). Similarly, in spt6 mutants there is slow histone redeposition at PHO5 , and nucleosomes are generally depleted from highly transcribed genes (Ivanovska et al 2011).…”
Section: Histone Dynamics: Mechanismmentioning
confidence: 59%
“…In multiple studies, yeast lacking various histone chaperones exhibit slowed H3/H4 turnover dynamics. This has been observed globally for Asf1 Kaplan et al 2008), Rtt106 (Imbeault et al 2008), and the CAF-1 and Hir complexes (Rosa et al 2010), although spt16 mutants, as cited above, do show increased turnover (Jamai et al 2009). Similarly, in spt6 mutants there is slow histone redeposition at PHO5 , and nucleosomes are generally depleted from highly transcribed genes (Ivanovska et al 2011).…”
Section: Histone Dynamics: Mechanismmentioning
confidence: 59%
“…By comparing Cse4 ChIP-Seq profiles in the presence or absence of SCM3 , we found that Cse4 binding sites in both genotypes were highly concordant (Figure S11; Spearman's ρ = 0.85; P<10 −15 ), suggesting that non-centromeric localization of Cse4 does not require Scm3. This finding is supported by the fact that transient incorporation of Cse4 on non-centromeric sites occurs at regions of high histone turnover, linking this phenomenon with nucleosome incorporation and ejection dynamics [37]. Cse4-containing nucleosome physical structure might also provide some potential reasons for the Scm3-independent Cse4 incorporation at non-centromeric loci.…”
Section: Resultsmentioning
confidence: 80%
“…Ubiquitin-mediated proteolysis appears to be a conserved mechanism to inhibit the assembly of CENP-A at ectopic loci by controlling CENP-A protein level (Collins et al, 2004; Gonzalez et al, 2014; Moreno-Moreno et al, 2006). CENP-A also can mis-incorporate to euchromatic region if histone H3 chromatin integrity is perturbed (Au et al, 2008; Choi et al, 2012; Lopes da Rosa et al, 2011). Recently, the H2A.Z homolog Pht1 in fission yeast has been implicated in the exclusion of CENP-A from non-centromeric chromatin (Ogiyama et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining the H3 nucleosome integrity is important for preventing mis-incorporation of CENP-A. Changes in histone H3 level, or mutations in histone chaperones and the FACT chromatin remodeling complex can lead to promiscuous CENP-A incorporation, likely due to disturbance of H3 chromatin integrity (Au et al, 2008; Choi et al, 2012; Lacoste et al, 2014; Lopes da Rosa et al, 2011). Ubiquitin-mediated proteolysis is another mechanism implicated in protecting euchromatic regions from assembling ectopic CENP-A chromatin (Au et al, 2013; Choi et al, 2012; Collins et al, 2004; Moreno-Moreno et al, 2006).…”
Section: Introductionmentioning
confidence: 99%